KAJIAN PENERAPAN PRINSIP WATER CONSERVATION SESUAI STANDAR GREENSHIP NEW BUILDING VERSI 1.2 STUDI KASUS: GEDUNG P1 DAN P2 UNIVERSITAS KRISTEN PETRA SURABAYA - Teddy, Steviani Dewi (JURNAL DIMENSI UTAMA TEKNIK SIPIL, 2015)
Nowadays, green building issue has become very important. The main reason is that buildings consume much of natural resources, in the middle of world energy and water crisis which is happening around the world. The goal of this research is to find out how much water saving that P1 and P2 building can achieve by applying the concepts of water saving fixture usage, rainwater harvesting, and grey water recycling. This saving is related to how many points that bulding can potentially achieve for WAC 1 to WAC 6 credit according to Greenship for New Building version 1.2 standard. Â To predict water consumption at P1 and P2 buildings, a questionnaire survey was conducted. Occupants of P, W, and T buildings of Petra Christian University Surabaya were randomly chosen as respondents. As the result of this research, P1 and P2 building original design is potential to achieve 17 points out of total 20 points. Suggestions are proposed to perfect the design of P1 and P2 building in order to achieve maximum 20 points.